The influence of Aquahatch on the growth performance of larval and juvenile African catfish (Clarias gariepinus, Burchell 1822) - Joscelyne, Mark (Stellenbosch : Stellenbosch University, 2020)
Thesis (MScAgric)--Stellenbosch University, 2020.